Geodesic mappings of quasi-Einstein spaces with a constant scalar curvature - V. A. Kiosak; G. V. Kovalova (Математичні Студії, 2020)
In this paper we study a special type of pseudo-Riemannian spaces - quasi-Einstein spaces of constant scalar curvature. These spaces are generalizations of known Einstein spaces. We obtained a linear form of the basic equations of the theory of geodetic mappings for these spaces. The studies are conducted locally in tensor form, without restrictions on the sign and signature of the metric tensor.